Misconceptions and stereotypes regarding experts providing support for risk-informed decision making. Issue 1 (2nd January 2019) - Maes, Marc A.
ABSTRACT: Support for high-level technical and environmental risk assessment and for large-scale decision making in general is typically provided by qualified experts. Often praised, but also reviled and blamed, the expert dwells in a cocoon of models and expertise and is armed with algorithms, regulations, and technical procedures to justify the support provided. At the end of the day experts often find themselves in sensitive and confrontational situations, as communication about highly uncertain issues is inherently 'risky'. The objective of this paper is to throw some light on common misconceptions about the expert's role in decision making. Various ill-conceived perceptions and stereotypes are organised in a set of widespread myths or misconceptions which the paper attempts to debunk in a neutral and objective manner. Certain types of flawed behaviour of individuals and organisations that portray themselves as decision making support experts, are also identified. They are categorised into a set of negative stereotypes that should raise red flags in dealing with such experts. The analysis of shortcomings, flaws, and misconceptions presented in this paper carries with it the benefit of providing solutions for a stronger and improved practice of risk-informed decision making.